THE SYSTEMATIC REVIEW OF RADIOLOGIC IMAGING IN SUSPECTED RENAL COLIC - Nuswantoro, Yoga; Anggraini, Efa (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Renal colic, a common cause of morbidity, is characterized by acute, intermittent flank pain. Diagnosis involves a combination of history, physical exam, laboratory testing, and imaging studies. In recent years, the assessment of individuals suspected of having renal colic has become increasingly dependent on imaging. Renal ultrasound is not reliable for seeing ureteral calculi and may miss smaller stones. Besides, the use of CT increased radiation exposure and high medical costs. The aim: This study aims to determine the radiologic imaging in patients with suspected renal colic. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like PubMed and ScienceDirect, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Results: In the PubMed database, the results of our search brought up 162 articles, whereas the results of our search on ScienceDirect brought up 135 articles. The results of the search conducted by title screening yielded a total 25 articles for PubMed and 15 articles for ScienceDirect. We compiled a total of 21 papers, 17 of which came from PubMed and 4 of which came from ScienceDirect. We excluded 2 review articles, 4 duplicate articles, 1 non-full text article, 1 article having ineligible subject and 4 articles having insufficient outcomes data. In the end, we included nine research that met the criteria. Conclusion: The use of point-of-care ultrasound (POCUS) in patients with suspected renal colic may avoid the use of CT. Although, the accuracy is lower than CT, but it can reduce medical expense and induced radiation exposure.